Distinct communication patterns of trophoblastic miRNA among the maternal-placental-fetal compartments. (December 2018) - Paquette, Alison G.; Chu, Tianjiao; Wu, Xiaogang; Wang, Kai; Price, Nathan D.; Sadovsky, Yoel
Abstract: Introduction: The placenta produces microRNAs (miRNA) that may traffic to the maternal or fetal compartments and influence the physiology of pregnancy. The trafficking patterns of miRNA expressed from the large human chromosome 19 and chromosome 14 clusters (C19MC and C14MC), remains unclear. We interrogated the cross-sectional landscape of miRNA expression within the human placenta, fetal and maternal plasma to elucidate miRNA trafficking. We hypothesized that C19MC and C14MC miRNAs have similar expression patterns across the maternal-fetal compartments. Methods: Placental biopsies, maternal and fetal venous plasma were collected from 25 pregnancies, and RNA was quantified using next generation sequencing. We identified expression and correlations differences among the compartments, and uncovered distinct miRNA expression patterns using consensus clustering. Results: We found that the placenta exhibits the highest total abundance, average miRNA expression and lowest variance of both C19MC and C14MC miRNAs. The C19MC miRNAs had a comparable expression and variance in fetal and maternal plasma and higher expression in the placenta. In contrast, the C14MC miRNAs had comparable expression between the placenta and fetal plasma, which was higher than the maternal plasma. We also identified 5 distinct groups of trophoblastic miRNAs with different expression patterns in each compartment. Discussion: This is the first comprehensive analysis of C19MC and C14MC miRNA expression patterns in the human placental, maternal and fetal compartments. Our findings suggest that C14MC miRNAs are produced by both the fetus and placenta, but C19MC miRNAs are produced primarily in the placenta and are trafficked to the fetal and maternal compartments. Highlights: The C19MC and C14MC are highly expressed in the placenta. C19MC miRNAs are abundant in the placenta and lower in the maternal-fetal plasma. C14MC miRNAs are similarly abundant in the placenta and fetal plasma. The C19MC and C14MC miRNA expression landscape forms 5 distinct clusters. C14MC, but not C19MC miRNAs, are likely produced by both the placenta and fetus.